2018
DOI: 10.1007/s10803-018-3493-1
|View full text |Cite
|
Sign up to set email alerts
|

Family Experiences with the Diagnosis of Autism Spectrum Disorder: System Barriers and Facilitators of Efficient Diagnosis

Abstract: This paper examines family experiences with the efficiency of ASD diagnosis. Children were age 8 or younger with ASD (n = 450). Outcomes were delay from first parent concern to diagnosis, shifting diagnoses, and being told child did not have ASD. Predictors were screening, travel distance, and problems finding providers. Logit models were used to examine associations. Screening was associated with reduced delay in diagnosis; problems finding providers were associated with greater delay. Screening, travel dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 41 publications
4
32
0
4
Order By: Relevance
“…Factors associated with age at ASD diagnosis. Of the 56 studies, 10 did not report any influencing factors on age at diagnosis (Cawthorpe, 2018;Garrido et al, 2018;Hausman-Kedem et al, 2018;Lo et al, 2017;Martinez et al, 2018;Masri et al, 2013;May et al, 2017;Mpaka et al, 2016;Nadeem et al, 2019;Ribeiro et al, 2017). However, 46 studies reported many possible influencing factors on age at ASD diagnosis, including type of ASD diagnosis, additional diagnoses and gender among the most frequently reported (Supplemental Material 2).…”
Section: Additional Analysesmentioning
confidence: 99%
“…Factors associated with age at ASD diagnosis. Of the 56 studies, 10 did not report any influencing factors on age at diagnosis (Cawthorpe, 2018;Garrido et al, 2018;Hausman-Kedem et al, 2018;Lo et al, 2017;Martinez et al, 2018;Masri et al, 2013;May et al, 2017;Mpaka et al, 2016;Nadeem et al, 2019;Ribeiro et al, 2017). However, 46 studies reported many possible influencing factors on age at ASD diagnosis, including type of ASD diagnosis, additional diagnoses and gender among the most frequently reported (Supplemental Material 2).…”
Section: Additional Analysesmentioning
confidence: 99%
“…Children living in geographically rural areas may have limited access to early, intensive evidencebased interventions suggesting children residing in these areas are less likely to experience positive outcomes than their urban-dwelling peers (Mello, Goldman, Urbano, & Hodapp, 2016). Access to trained providers is also identified as a barrier for rural families as they are often made to wait their turn for services or face additional costs to travel long distances to obtain necessary services widening the equity gap due to geographical location (Martinez et al, 2018).…”
Section: Access For Families In Rural Areasmentioning
confidence: 99%
“…The family-centered approach of P-ESDM aligns with the state's primary service provider model in which one member of the multidisciplinary team is selected to be the family's primary contact for early intervention services. Likewise, our state faces persistent personnel shortages in early childhood intervention, often cited as a barrier to accessing high quality services for families living in rural and remote areas (Martinez et al, 2018). For this reason, telehealth was chosen as the means for implementation of P-ESDM.…”
Section: Independent Variable (Iv)mentioning
confidence: 99%
“…Others report they are not well prepared to identify children or comfortable talking with families about ASD concerns (Crais et al, 2014), including those from Latino families (Zuckerman et al, 2013). Despite high self-reports of pediatric screening (Self et al, 2015), in a recent survey of caregivers of young children with ASD, only half reported their child was screened for ASD (Martinez et al, 2018). However, some families may not be aware of screening if they do not complete a form and are asked questions orally.…”
mentioning
confidence: 99%